Investigating depression pathways in a clinical sample: childhood adversity, reward, and threat processing - Oltean, Lia-Ecaterina; Miu, Andrei C.; Szentágotai-Tǎtar, Aurora (Frontiers in Psychology, 2025)
Childhood adversity (CA, abuse and neglect) is an important risk factor for depression. However, other variables, such as childhood socioeconomic status (SES), may influence this association. Moreover, the underlying mechanisms that contribute to the devastating consequences of CA for depression are incompletely understood. Still, recent work point toward reward and threat processing. Building on these, we sought (1) to investigate associations between CA, depression, reward and threat processing, (2) to control for childhood SES when investigating these associations, and (3) to test the mediating role of reward and threat processing in the association between CA and depression. Inpatients (N = 33, m = 48.36; SD = 11.76) with a formal diagnosis of major depressive disorder completed self-report measures for all variables of interest. We found significant associations between CA, depression and threat processing, but no other significant associations emerged (p < 0.05). Results remained similar when we controlled for childhood SES. Furthermore, we did not find support for the potential mediating role of reward and threat processing in the association between CA and depression. These results extend existing research investigating CA and depression, and single out threat processing. Moreover, they suggest that these patterns of associations are robust. While they do not provide support for the proposed mechanisms, they underscore the need for further research and point out relevant directions.